Ternary single-crystal positive electrode material and preparation method and application thereof

By the use of excessive lithium and atomized gas -phase deposition process in the ternary positive material to form a covering layer of lithium manganate and lithium manganese -rich material materials, it solves the uniform granules and the crystal structure of the traditional ternary positive material preparation process. The problem has significantly increased the battery capacity and cycle life.

CN119370905APending Publication Date: 2025-01-28HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411419374.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

During the preparation process, traditional ternary positive electrode materials have problems such as uneven particle size and unstable crystal structure, which affects their electrochemical properties.

Method used

The three yuan front -drive body of high -surface residual alkali is prepared by excessive lithium with an excessive lithium, and the layer of lithium manganate and lithium manganese -rich material materials on the surface of the ternary single crystal surface through the atomized gas phase deposition process.

Benefits of technology

A uniform covering of the ternary single crystal positive material is achieved, the stability of the material and the capacity and cycle life of the battery are improved, and it provides new ideas for battery pre -lithium technology.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119370905A_ABST
    Figure CN119370905A_ABST
Patent Text Reader

Abstract

The invention provides a ternary single-crystal positive electrode material as well as a preparation method and application thereof, and relates to the technical field of lithium ion batteries. A preparation method of a ternary single-crystal positive electrode material comprises the following steps: S1, uniformly mixing a ternary precursor with a lithium source to obtain a mixture, performing primary sintering treatment on the mixture, and performing crushing and sieving to obtain a primary sintering material; and S2, transferring the primary sintering material into a calcining furnace, spraying the vaporific atmosphere of the manganese salt solution and oxygen into the calcining furnace for secondary sintering, and crushing and sieving to obtain the ternary single crystal positive electrode material. The ternary single crystal positive electrode material provided by the invention is helpful for improving the capacity and cycle performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium-ion batteries, and in particular to a ternary single crystal positive electrode material and a preparation method and application thereof. Background Art

[0002] With the rapid development of electronic products such as electric vehicles and smart phones, the demand for high-performance lithium-ion batteries is growing. As a vital component of lithium-ion batteries, the performance of positive electrode materials directly determines key indicators such as battery capacity, energy density, and cycle life. Among the many positive electrode materials, ternary materials (such as NMC, NCA, etc.) have attracted much attention due to their high energy density and excellent electrochemical properties. However, traditional ternary materials often have some problems in the preparation process, such as uneven particles and unstable crystal structure, which will affect the electrochemical properties of the materials. In order to solve these problems, researchers are constantly exploring new preparation methods and surface modification technologies to improve the performance of ternary materials.

[0003] Among the many surface modification technologies, surface coating is a common and effective method. By coating one or more layers of materials on the surface of the positive electrode material, the surface structure of the material can be improved, the stability of the material can be improved, and the performance of the battery can be optimized. At present, a variety of materials have been used as coating layers for ternary materials, such as alumina, zirconium oxide, silicate, etc. However, although these coating materials can improve the cycle performance of the material and reduce electrolyte erosion, there is no significant improvement in capacity, and the cycle improvement is not obvious.

[0004] In recent years, the material pre-lithiation technology has attracted many researchers to conduct in-depth research. Among them, lithium ferrite (LiFeO2) and lithium nickel oxide (LiNiO2) have attracted much attention due to their high capacity. By mixing a small amount of these materials into the positive electrode material, the pre-lithiation effect can be achieved during the first charge and discharge process, thereby improving the capacity and cycle life of the battery. However, such materials have poor air stability, are easy to deliquesce, and are easy to produce gas when preparing batteries, which still poses some challenges in practical applications. Summary of the invention

[0005] Based on the technical problems existing in the background technology, the present invention proposes a ternary single crystal positive electrode material and a preparation method and application thereof.

[0006] The present invention provides a method for preparing a ternary single crystal positive electrode material, comprising the following steps:

[0007] S1. Evenly mix the ternary precursor and the lithium source to obtain a mixture, and perform a sintering treatment on the mixture, and crush and screen to obtain a fired material;

[0008] S2. The primary sintered material is transferred into a calcining furnace, and the mist atmosphere of the manganese salt solution and oxygen are sprayed into the calcining furnace for secondary sintering. After crushing and screening, the ternary single crystal positive electrode material is obtained.

[0009] The present invention allows more residual alkali to remain on the surface of the single crystal by burning excess lithium, sprays and atomizes a manganese sulfate solution, and introduces it into a furnace together with oxygen gas, so that it reacts with the residual alkali Li on the surface of the single crystal at high temperature and is deposited on the surface of the single crystal to form a coating layer of a mixture of lithium manganate and lithium-rich manganese material. The prepared positive electrode material is charged at a high voltage of 4.8V in the first cycle of assembled battery, so that the lithium manganate and lithium-rich manganese material, the coating materials formed by sintering on the surface of the positive electrode single crystal material, are largely delithiated, achieving a pre-lithium effect, effectively improving the capacity and cycle life of the battery, and providing a new idea for battery pre-lithium technology.

[0010] Preferably, in the S1, the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, wherein 0.5≤x<1, 0<y≤0.2.

[0011] Preferably, in S1, the lithium source is selected from one or more of lithium carbonate and lithium hydroxide.

[0012] The selection of the type of lithium source helps to control the particle size of the single crystal particles.

[0013] Preferably, in S1, the molar ratio of lithium in the lithium source to the ternary precursor transition metal is (1.1-1.3):1.

[0014] The molar ratio of lithium in the lithium source to the ternary precursor transition metal is helpful to control the residual alkali content of the material and the degree of lithium-nickel mixing within a certain range.

[0015] Preferably, in S1, the primary sintering treatment comprises heating the temperature to 750-950°C at a heating rate of 2-10°C / min, keeping the temperature for 10-20h, and cooling the temperature to room temperature at a cooling rate of 1-5°C / min.

[0016] Controlling the conditions of the primary sintering helps control the size of the single crystal particles, thereby effectively controlling the material capacity and rate performance.

[0017] Preferably, in said S1, the residual alkali on the surface of the calcined material is LiOH ≥ 0.3wt%, and Li2CO3 ≥ 0.6wt%.

[0018] Preferably, in S1, the D50 particle size after crushing and screening is 3.5±0.3 μm.

[0019] Preferably, in S1, the particle size after crushing and screening meets (D90-D10) / D50≤1.5.

[0020] Preferably, in S2, the calcining furnace is a CVD furnace.

[0021] Preferably, in S2, the manganese salt is selected from one or more of manganese sulfate, manganese nitrate and manganese chloride.

[0022] Preferably, in the S2, the concentration of the manganese salt solution is 1-2 mol / L.

[0023] Controlling the concentration of the manganese salt solution within a certain range helps control the coating thickness.

[0024] Preferably, in S2, the gas flow ratio of the mist atmosphere of the manganese salt solution and oxygen is (0.5-0.8):1.

[0025] The manganese sulfate solution is sprayed and atomized, and then introduced into the furnace together with oxygen gas. At high temperature, it reacts with the residual alkali Li on the surface of the single crystal and is deposited on the surface of the single crystal to form a coating layer of lithium manganate and a mixture of lithium-rich manganese materials. This method not only solves the problems existing in traditional coating technology and realizes uniform surface coating of the single crystal, but also the coated material has a pre-lithium effect, which effectively improves the capacity and cycle life of the battery, and provides a new idea for battery pre-lithium technology. By controlling the ratio of the mist atmosphere of the manganese salt solution and the gas flow rate of oxygen within a certain range, it helps the lithium-rich manganese-based material to react fully and completely on the surface.

[0026] Preferably, in S2, the secondary sintering treatment comprises heating to 700-800°C at a heating rate of 2-10°C / min, keeping the temperature for 3-8h, and cooling to room temperature at a cooling rate of 1-5°C / min.

[0027] Controlling the conditions of the secondary sintering treatment helps to reduce the residual alkali on the surface and form a lithium-rich manganese-based coating layer on the surface of the material.

[0028] Preferably, in the S2, the residual alkali on the surface of the ternary single crystal positive electrode material LiOH≤0.2wt%, Li2CO3≤0.3wt%.

[0029] Preferably, in the S2, the molar ratio of the residual alkali Li on the surface of the calcined material to the Mn in the manganese salt is (1.2-2):1.

[0030] Controlling the molar ratio of residual alkali Li on the surface of the calcined material to Mn in the manganese salt within a certain range is helpful for the complete synthesis reaction of lithium-rich manganese-based materials on the surface and for higher capacity utilization.

[0031] Preferably, the coating layer of the ternary single crystal positive electrode material has a thickness of 200 to 500 nm.

[0032] The present invention also provides a ternary single crystal positive electrode material prepared by the above preparation method.

[0033] A lithium ion positive electrode plate comprises the above-mentioned ternary single crystal positive electrode material or the ternary single crystal positive electrode material prepared by the above-mentioned preparation method.

[0034] A lithium-ion battery comprises the above-mentioned lithium-ion positive electrode plate.

[0035] Preferably, the first cycle charging voltage of the lithium-ion battery after being fully charged is ≥4.8V.

[0036] The beneficial effects of the present invention are:

[0037] The present invention adopts a high surface residual alkali-burned material prepared by excessive lithium addition and sintered with atomized manganese sulfate to realize the vapor deposition of nano-scale lithium manganate and lithium-rich manganese-based materials on the surface of ternary single crystals, and the coating surface is uniform, which effectively stabilizes the crystal structure; at the same time, the innovative atomized vapor deposition process is used to realize the direct coating reaction on the surface of the ternary single crystal to form a pre-lithium material. Compared with the traditional physical blending pre-lithium material, the capacity and cycle performance are significantly improved, and the material particles are more uniform and stable. The present invention can meet the design and requirements of high energy density long cycle batteries, and has broad prospects for application in the power battery market. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 This is the SEM image of the ternary single crystal positive electrode material prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0039] The technical solution of the present invention is described in detail through specific embodiments.

[0040] Unless otherwise specified, the materials, reagents, etc. used in the following examples and comparative examples can be obtained from commercial sources.

[0041] Example 1

[0042] A method for preparing a ternary single crystal positive electrode material comprises the following steps:

[0043] S1, lithium carbonate, ternary precursor Ni 0.6 Co 0.2 Mn 0.2 (OH)2 is mixed evenly with lithium in lithium carbonate and ternary precursor transition metal nickel, cobalt and manganese in a molar ratio of 1.2:1 to obtain a mixture, and the mixture is sintered once in an oxygen atmosphere, heated to 900°C at a heating rate of 2°C / min, kept warm for 15 hours, cooled to room temperature, crushed and sieved to obtain a calcined material; the surface residual alkali of the calcined material is 0.623% Li2CO3 and 0.319% LiOH;

[0044] S2. The first-fired material is transferred into a CVD furnace, 1 mol / L manganese sulfate is sprayed, and a mist atmosphere and oxygen are jointly introduced into the CVD furnace at a gas flow ratio of 0.5:1 for secondary sintering. The temperature is raised to 750°C at a heating rate of 2°C / min, and the temperature is kept for 5 hours. After crushing and screening, a ternary single crystal positive electrode material with D10 of 1.5μm, D50 of 3.6μm, and D90 of 6.7μm is obtained, wherein the molar ratio of residual alkali Li on the surface of the first-fired material to Mn of manganese sulfate is 1.5:1.

[0045] Example 2

[0046] A method for preparing a ternary single crystal positive electrode material comprises the following steps:

[0047] S1, lithium carbonate, ternary precursor Ni 0.7 Co 0.1 Mn 0.2 (OH)2 is mixed evenly with lithium in lithium carbonate and ternary precursor transition metal nickel, cobalt and manganese in a molar ratio of 1.25:1 to obtain a mixture, and the mixture is sintered once in an oxygen atmosphere, heated to 880°C at a heating rate of 2°C / min, kept warm for 15 hours, cooled to room temperature, crushed and sieved to obtain a calcined material; the surface residual alkali of the calcined material is 0.657% Li2CO3 and 0.335% LiOH;

[0048] S2. The first-fired material is transferred into a CVD furnace, sprayed with 1.5 mol / L manganese sulfate, and then the mist atmosphere and oxygen are jointly introduced into the CVD furnace at a gas flow ratio of 0.6:1 for secondary sintering. The temperature is raised to 800°C at a heating rate of 2°C / min, and the temperature is kept for 5 hours. After crushing and screening, a ternary single crystal positive electrode material with a D10 of 1.3 μm, a D50 of 3.5 μm, and a D90 of 6.8 μm is obtained, wherein the molar ratio of the residual alkali Li on the surface of the first-fired material to the Mn of manganese sulfate is 1.8:1.

[0049] Example 3

[0050] A method for preparing a ternary single crystal positive electrode material comprises the following steps:

[0051] S1, lithium hydroxide, ternary precursor Ni 0.8 Co 0.1 Mn 0.1 (OH)2 is mixed evenly with lithium in lithium hydroxide and ternary precursor transition metal nickel, cobalt and manganese in a molar ratio of 1.12:1 to obtain a mixture, and the mixture is sintered once in an oxygen atmosphere, heated to 850°C at a heating rate of 2°C / min, kept warm for 15 hours, cooled to room temperature, crushed and sieved to obtain a calcined material; the surface residual alkali of the calcined material is 0.724% Li2CO3 and 0.336% LiOH;

[0052] S2. The first-fired material is transferred into a CVD furnace, sprayed with 2 mol / L manganese sulfate, and then the mist atmosphere and oxygen are jointly introduced into the CVD furnace at a gas flow ratio of 0.8:1 for secondary sintering. The temperature is raised to 700°C at a heating rate of 2°C / min, and the temperature is kept for 5 hours. After crushing and screening, a ternary single crystal positive electrode material with a D10 of 1.4 μm, a D50 of 3.4 μm, and a D90 of 6.5 μm is obtained, wherein the molar ratio of the residual alkali Li on the surface of the first-fired material to the Mn of manganese sulfate is 1.2:1.

[0053] Example 4

[0054] A method for preparing a ternary single crystal positive electrode material comprises the following steps:

[0055] S1, lithium hydroxide, ternary precursor Ni 0.9 Co 0.04 Mn 0.06 (OH)2 is mixed evenly with lithium in lithium hydroxide and ternary precursor transition metal nickel, cobalt and manganese in a molar ratio of 1.1:1 to obtain a mixture, and the mixture is sintered once in an oxygen atmosphere, heated to 820°C at a heating rate of 2°C / min, kept warm for 15 hours, cooled to room temperature, crushed and sieved to obtain a calcined material; the surface residual alkali of the calcined material is 0.785% Li2CO3 and 0.382% LiOH;

[0056] S2. The first-fired material is transferred into a CVD furnace, 1 mol / L manganese sulfate is sprayed, and a mist atmosphere and oxygen are jointly introduced into the CVD furnace at a gas flow ratio of 0.6:1 for secondary sintering. The temperature is raised to 700°C at a heating rate of 2°C / min, and the temperature is kept for 5 hours. After crushing and screening, a ternary single crystal positive electrode material with D10 of 1.4μm, D50 of 3.6μm, and D90 of 7.1μm is obtained, wherein the molar ratio of residual alkali Li on the surface of the first-fired material to Mn of manganese sulfate is 1.3:1.

[0057] Comparative Example 1

[0058] A method for preparing a ternary single crystal positive electrode material comprises the following steps:

[0059] S1, lithium carbonate, ternary precursor Ni 0.6 Co 0.2 Mn 0.2 (OH)2 is mixed evenly with lithium in lithium carbonate and ternary precursor transition metal nickel, cobalt and manganese in a molar ratio of 1.05:1 to obtain a mixture, and the mixture is sintered once in an oxygen atmosphere, heated to 900°C at a heating rate of 2°C / min, kept warm for 15 hours, cooled to room temperature, crushed and sieved to obtain a ternary single crystal positive electrode material with D10 of 1.6μm, D50 of 3.5μm and D90 of 6.6μm; the surface residual alkali Li2CO3 is 0.205%, and LiOH is 0.153%.

[0060] Comparative Example 2

[0061] The ternary single crystal positive electrode material of comparative example 1 and 1% lithium nickelate LiNiO2 pre-lithium material are uniformly mixed to obtain a positive electrode material.

[0062] The above materials were used as positive electrode active material powders, and were mixed with conductive carbon black SP powder and binder 5wt% polyvinylidene fluoride PVDF solution (solvent is N-methylpyrrolidone) in a mass ratio of 95:2:3 to form a slurry, and then evenly coated on carbon-coated aluminum foil, and then placed in a vacuum oven to dry for 8 hours to obtain a positive electrode sheet; the positive electrode sheet was also assembled into a single-piece soft-pack battery in an argon environment glove box with a PP diaphragm, a graphite negative electrode sheet, and an electrolyte, and the first cycle charging was performed at a voltage of 2.8 to 4.8V using 0.1C to activate pre-lithium, and then the rate and cycle tests were performed. The test results are shown in Table 1.

[0063] Table 1

[0064]

[0065]

[0066] It can be seen from the data in Table 1 that, compared with Comparative Example 1, the capacity of Example 1 of the present invention is increased by 3.5 mAh / g after coating, and the cycle is greatly improved. Compared with Comparative Example 2 using nickel oxide blended pre-lithium, the cycle performance still has great advantages, which is sufficient to illustrate that the nickel oxide manganese and lithium-rich manganese-based coated ternary single crystal pre-lithium materials prepared by the innovative process of vapor deposition reaction on the single crystal surface of the present invention effectively improve the cycle performance and provide a new idea for the development of pre-lithium materials.

[0067] Figure 1 This is the SEM picture of Example 1. It can be seen from the picture that the sintered finished material has a single crystal particle morphology, and the surface of the single crystal particle is coated with lithium manganese oxide and lithium-rich manganese-based materials.

[0068] In summary, the ternary single crystal positive electrode material provided by the present invention has good stability and helps to improve the capacity and cycle performance of the battery.

[0069] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A method for preparing a ternary single crystal positive electrode material, characterized in that: The following steps are involved: S1. Evenly mix the ternary precursor and the lithium source to obtain a mixture, and perform a sintering treatment on the mixture, and crush and screen to obtain a fired material; S2, transferring the primary calcined material into a calcining furnace, spraying the mist atmosphere of the manganese salt solution and oxygen into the calcining furnace for secondary sintering, and obtaining a ternary single crystal positive electrode material after crushing and screening; In the S1, the ternary precursor is Ni x Co y Mn 1-x-y (OH)2, wherein 0.5≤x<1, 0<y≤0.

2.

2. The preparation method according to claim 1, characterized in that: In the S1, the lithium source is selected from one or more of lithium carbonate and lithium hydroxide.

3. The preparation method according to claim 1, characterized in that: In the S1, the molar ratio of lithium in the lithium source to the ternary precursor transition metal is (1.1-1.3):

1.

4. The preparation method according to claim 1, characterized in that: In the above-mentioned S1, the primary sintering treatment includes heating to 750-950°C at a heating rate of 2-10°C / min, keeping the temperature for 10-20h, and cooling to room temperature at a cooling rate of 1-5°C / min.

5. The preparation method according to claim 1, characterized in that: In the S2, the concentration of the manganese salt solution is 1-2 mol / L.

6. The preparation method according to claim 1, characterized in that: In the S2, the gas flow ratio of the mist atmosphere of the manganese salt solution and oxygen is (0.5-0.8):

1.

7. The preparation method according to claim 1, characterized in that: In the above-mentioned S2, the secondary sintering treatment includes heating to 700-800°C at a heating rate of 2-10°C / min, keeping the temperature for 3-8h, and cooling to room temperature at a cooling rate of 1-5°C / min.

8. The preparation method according to claim 1, characterized in that: In the S2, the molar ratio of the residual alkali Li on the surface of the calcined material to the Mn in the manganese salt is (1.2-2):

1.

9. A ternary single crystal positive electrode material, characterized in that: The compound is prepared by the preparation method according to any one of claims 1 to 8.

10. A lithium-ion positive electrode plate, comprising the ternary single crystal positive electrode material according to claim 9 or the ternary single crystal positive electrode material prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Coating method of high-nickel ternary material

    CN109686931A

  • Positive electrode material, preparation method thereof and lithium ion battery

    CN111628157A

  • Water-washing-free coating method for high-nickel positive electrode material

    CN113809287A

  • Spray-coated lithium nickel manganese oxide positive electrode material method

    CN113937256A

  • Ternary positive electrode material having core-shell structure and preparation method therefor, and lithium ion battery

    WO2024146003A1